Analisis Kebijakan Pemerintah Menambah Kadar CPO pada BBM Biosolar dalam Upaya Menghemat Devisa Negara Indonesia - Sri Indah Siregar; Masitah Khairani; Faisal Aqasah; Willi Ardianto; Dwita Sakuntala (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
In the implementation of the manufacture of BioSolar or BioDiesel fuel, the government uses a hybrid concept which is by mixing diesel from petroleum with Crude Palm Oil (CPO), this policy is useful in saving the country's foreign exchange where the government reduces the amount of petroleum imports and replaces it with CPO from within the country. Because Indonesia is one of the largest CPO producing countries in the world, through this policy the government can make better use of Indonesia's natural resources. This study uses a qualitative research method with a descriptive approach where researchers observe a phenomenon of increasing levels of palm oil (CPO) in current diesel fuel, namely from B30 to B35.